Impact of sintering conditions and zirconia addition on flexural strength and ion conductivity of Na-β"-alumina ceramics. (June 2020) - Bay, Marie-Claude; Heinz, Meike V.F.; Linte, Cristina; German, Alexander; Blugan, Gurdial; Battaglia, Corsin; Vogt, Ulrich F.
Highlights: Zirconia addition to Na-β"-alumina ceramics increases the flexural strength by 30 %. In presence of zirconia, the onset temperature of liquid phase formation in Na-β"-alumina ceramics is reduced by 60 °C. Thus, zirconia addition enables processing of Na-β"-alumina at lower sintering temperatures. Abstract: Na-β"-alumina ceramics are applied as electrolytes in high-temperature Na/NiCl2 and Na/S batteries. Although featuring excellent sodium-ion conductivity in the order of 0.2 S cm −1 at 300 °C, the brittleness associated with ceramic materials makes Na-β"-alumina electrolytes vulnerable to mechanical stresses, e.g. during battery operation. In this study, the impact of grain size and density on the flexural strength of Na-β"-alumina ceramics is investigated. For constant composition but largely varying grain sizes, we report a constant flexural strength of 163 ± 10 MPa for sintering temperatures between 1560 °C and 1620 °C and dwell times ≤ 30 min. Addition of 5 vol % zirconia improves the flexural strength by 30 %, but reduces the conductivity by 15 %. Furthermore, we show that the addition of zirconia reduces the onset temperature of the liquid phase formation during sintering. These findings show promise for using lower sintering temperatures in the presence of zirconia, which is beneficial on an industrial level.